2015
DOI: 10.1103/physreva.91.052122
|View full text |Cite
|
Sign up to set email alerts
|

Floquet control of quantum dissipation in spin chains

Abstract: Controlling the decoherence induced by the interaction of quantum system with its environment is a fundamental challenge in quantum technology. Utilizing Floquet theory, we explore the constructive role of temporal periodic driving in suppressing decoherence of a spin-1/2 particle coupled to a spin bath. It is revealed that, accompanying the formation of a Floquet bound state in the quasienergy spectrum of the whole system including the system and its environment, the dissipation of the spin system can be inhi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…The idea of controlling quantum dissipation via periodic driving is based on the correspondence between the quasienergy spectrum in a temporally periodic system and the energy spectrum in the static system [39]. Compared with the static case, the periodic driving provides a much flexible tool in manipulating the formation of the bound state.…”
Section: Floquet Control Of Quantum Dissipationmentioning
confidence: 99%
“…The idea of controlling quantum dissipation via periodic driving is based on the correspondence between the quasienergy spectrum in a temporally periodic system and the energy spectrum in the static system [39]. Compared with the static case, the periodic driving provides a much flexible tool in manipulating the formation of the bound state.…”
Section: Floquet Control Of Quantum Dissipationmentioning
confidence: 99%
“…Other quantum phenomena related to dynamical stabilization are coherent destruction of tunneling in a double-well potential [15][16][17], the localization of a moving charged particle under the action of a time-periodic electric field [18,19], and the localization of a wavepacket in a periodic lattice due to periodic shaking of the lattice [20][21][22][23] or modulating the inter-particle interactions [24]. In interacting quantum gases, a Kapitza or a dynamically stabilized state has different manifestations, for instance, stabilizing a Bose-Einstein condensate [25] or a bright soliton [26,27] against collapse, freezing spin mixing dynamics in spinor condensates [28][29][30], inhibiting dissipation from a spin-half particle [31], stabilizing a classically unstable phase (π-mode) in a bosonic Josephson junction [32], or giving rise to unconventional ordered phases that have no equilibrium counterparts [33]. Additionally, dynamical stabilization has been used to control the superfluid-Mott insulator quantum phase transition of bosons in an optical lattice [22].…”
Section: Introductionmentioning
confidence: 99%
“…Other than the above-listed protocols, it has also long been confirmed that temporal periodic driving on the open system can impose significant effects on the system dynamics [36][37][38][39][40][41][42]. Some methods of dealing with this problem, e.g., spectral filtering theory [43][44][45][46][47] and those based on the Floquet theory [48][49][50], have also been developed. Different from the bound states generated in the time-independent system, e.g., the impurity system in the solid system, the bound states generated by temporal periodic driving fields are time-dependent and are dubbed as Floquet bound states [48][49][50].…”
Section: Introductionmentioning
confidence: 99%